Nanotechnology for SARS-CoV-2 diagnosis - Khodadadi, Alisa; Zarepour, Atefeh; Abbaszadeh, Sepideh; Firoozi, Maryam; Bahrami-Banan, Fatemeh; Rabiee, Amir; Hassanpour, Mahnaz; Kermanian, Mehraneh; Pourmotabed, Samiramis; Zarrabi, Ali; Moradi, Omid; Yousefiasl, Sepideh; et al. (Nanofabrication, 2022)
As the first cause of death in the last three years, SARS-CoV-2 infection gained lots of interest. In light of this, several studies have been done to fabricate novel, high-speed detection methods for different virus variants. Indeed, the high mortality rate that could result from the late detection and the probable false results of conventional tests used to detect infection led to the introduction. Among the most interesting of them are -based biosensors fabricated from inorganic-based nanomaterials to diagnose SARS-CoV-2. Accordingly, this review paper presents an overview of recent nanotechnology advances in fabricating biosensors for diagnosing SARS-CoV-2 infections.